Integrated Improvement Of The Performance Of The Special Job Placement Center (BKK) of SMK Negeri 1 Sukorejo - Suryawati, Ririk; Nurjanah, Nunung (Jurnal Profesi Kependidikan, 2025)
This study aims to strengthen the performance of the Special Job Placement Center (BKK) at SMK Negeri 1 Sukorejo through simple digital-based innovations. Using a qualitative descriptive method with an experiential internship approach, data were collected via observation, participation, and documentation. The findings indicate that although BKK had a solid institutional foundation, it faced challenges in updating job vacancies, tracer studies, and digital interactivity. Implemented improvements standardized announcements, digital tracer tools, and recruitment documentation successfully enhanced service effectiveness, information accessibility, and data reliability for alumni and industry partners.